TANTANGAN DAN KESEMPATAN PEMENUHAN HAK PENDIDIKAN DASAR DAN MENEGAH DI KAWASAN PERBATASAN NEGARA DI PROVINSI KALIMANTAN BARAT - Endah Rantau Itasari (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Increasing access to education cannot be separated from the spatial use and utilization plan of the border area itself. Oftentimes, the Regional Spatial Planning (RTRW) which is intended for the opening and construction of schools at the village and sub-district levels becomes an obstacle to the program because it must be reviewed and changed, or simply violated. In fact, almost all of the licensing processes for the establishment of primary and secondary schools for private primary and secondary schools established by non-state entities are very difficult to obtain due to the unclear use and utilization of regional space. The number of permits issued has begun to be targeted by the DPRD for the fulfillment of PAD, so that issues that do not match the existing spatial plan are not taken seriously. In the end, sustainability as a principle and good governance as a practice which are two twin aspects of good spatial planning only exist in the concept because they only serve as tools to legitimize public sector malpractice in the use of space and exploitation of resources, especially in border areas. Permits to use space for the establishment of primary and secondary schools by the private sector should be adjusted to the state's alignment with increasing access to education.